Perlindungan Hukum Terhadap Perempuan Korban Kekerasan Dalam Rumah Tangga - Zainudin Hasan; Alika Firly; Adelia Putri Utami; Diah Eka Sari (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Domestic violence violates women's human rights. The form of violence that occurs in women is physical violence including assault, beating, and actions that physically injure the victim. Meanwhile, non-physical violence is an act that is detrimental to the victim from a psychological perspective, such as threats, insults, neglect and forms of violence that result in psychological disorders of the victim. In disclosing the existence of criminal acts of violence is the most difficult part for the authorities, because there are perspectives and risks that arise as a result of reports of acts of violence experienced by women. Women have the right to complain about illegal acts and receive protection under Law no. 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT), which allows for the settlement of cases of violence against women through the courts.